Outbreak of Bovine Herpetic Meningoencephalomyelitis in Southern Brazil - Wronski, Julia Gabriela; Cecco, Bianca Santana; Henker, Luan Cleber; Lorenzett, Marina Paula; Roehe, Paulo Michel; Finoketti, Fernando; Fetti, Thaís Moreira; Sonne, Luciana (Acta Scientiae Veterinariae, 2018)
Background: Herpetic meningoencephalitis is an infectious contagious disease worldwide distributed, most often caused by bovine alphaherpesvirus type 5 (BoHV-5), although bovine alphaherpesvirus type 1 (BoHV-1) may occasionally be the causative agent. The disease is characterized by subacute to acute clinical onset, often affecting animals submitted to stressful situations. Clinical signs are mainly neurologic due to meningoencephalitis and cortical necrosis. The involvement of the spinal cord has also been reported, however in BoHV-1 associated disease only. The aim of this report is to describe an outbreak of bovine meningoencephalomyelitis associated to BoHV-5. Case: In August 2017, nine 1-year-old calves died in a beef cattle farm with a flock of approximately 400 bovines. The animals presented neurological clinical signs characterized by excessive salivation, nasal and ocular discharges, incoordination, apathy, head tremors, head pressing, wide-based stance, recumbency followed by convulsions and paddling. According to the owner and referring veterinarian, affected animals displayed severe clinical signs with rapid progression and often leading to death in up to seven days. Four of these calves were submitted for necropsy, and gross lesions were present in the brain, characterized by mild to moderate multifocal hemorrhagic and soft areas. On cut surface, extensive areas of dark brown discoloration and malacia were observed. Histologically, lesions were characterized by extensive areas of liquefactive necrosis in the cerebral cortex grey matter, associated with inflammatory infiltrates composed of neutrophils, lymphocytes, plasma cells and foamy macrophages, as well as multifocal to coalescing areas of hemorrhage and fibrin deposition. Intranuclear eosinophilic inclusion bodies were rarely observed in neurons and astrocytes. On leptomeninges, there was diffuse inflammatory infiltrates of lymphocytes and plasma cells. Inflammation was also seen in a milder degree in the spinal cord, characterized by infiltrate of lymphocytes at grey matter, mainly around vessels. A herpesvirus which induced typical cytopathic effect in cell cultures was recovered from tissues. The isolated virus was typed as BoHV-5 by nucleotide sequencing analysis of the gC coding region. Discussion: The diagnosis of meningoencephalomyelitis associated to BoHV-5 was based on epidemiological, clinical, macroscopical, histological, virological and genomic findings. In the outbreak here reported, the disease occurred in young animals, with low morbidity but high lethality rates. Clinical signs on this case were consistent with previous reports on the literature. Bovines affected by BoHV-5 may display no gross lesions within the CNS; however, inflammatory and degenerative changes are frequently seen, characterized by malacia, leptomeningeal vessels hyperemia, edema and hemorrhages. Histologically, non-suppurative necrotizing meningoencephalitis is seen, with perivascular inflammatory infiltrates and, occasionally, intranuclear eosinophilic inclusion bodies in astrocytes and neurons. Similar but milder lesions were seen in the spinal cords of two of the necropsied calves, a feature which has only been previously associated to BoHV-1 infections. The identification of the implicated agent was accomplished by virus isolation in cell cultures followed by genome typing. Specific treatments for this condition are not currently available, and the number of animals that recover from clinically apparent disease is extremely low. Preventive measures are based on serological testing of herds, and segregation or elimination of seropositive calves. To avoid progression of the disease in seropositive animals, control efforts must be directed to avoid stressful conditions. Vaccination with BoHV-1 and BoHV-5 vaccines is expected to confer protection to clinical disease.